Results of a screening examination for the presence of markers of West Nile fever in the central and southern territories of Russia - S. K. Udovichenko; E. V. Putintseva; A. A. Baturin; L. A. Ryabinina; A. V. Toporkov (Медицинский вестник Юга России, 2024)
Objective: to study the intensity of contact with the causative agent of West Nile fever (WNF) of the population of certain central and southern territories of Russia.Materials and methods: the screening survey covered 1,230 people in 11 regions of the Russian Federation. The work used molecular genetic, immunological and statistical methods.Results: WNVmarkers, indicating an acute infectious process, were detected in 1.4% of samples. For the first time, local cases of the disease were confirmed in 9 regions of central Russia and the North Caucasus. The circulation of West Nile virus genotype 1 in the territory of the Republics of Ingushetia and Mordovia, genotype 2 in the Ivanovo and Nizhny Novgorod regions, Chuvash and Kabardino- Balkarian Republics is shown. The results of studying the immune layer revealed the presence of antibodies to the West Nile virus of the IgG class in 4.5% of the examined local population, with the highest rates in the Chechen Republic (10%) and the Republic of North Ossetia-Alania (14%). The maximum level of population immunity was noted among people in the age groups 20–29 years old and amounted to 9.7%, 30–39 years old – 7.8%.Conclusion: the results obtained significantly supplemented our understanding of the spread of WNV in Russia and the activity of disease foci, and can be used in planning and conducting monitoring studies.